Pemanfaatan Website sebagai Platform Promosi Digital Untuk Meningkatkan Minat Pariwisata Desa Bumiwangi - Dessy Pratama Aliyanti; Riska Apriliana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bumiwangi Village is one of the tourist villages located in Ciparay District, Bandung Regency, West Java. This tourist village offers a different tourist experience from other villages, namely enjoying the beauty of nature through hang gliding or paragliding sports from the top of Bukit Cula. However, Bumiwangi Village is still not widely recognized by the general public as a tourist destination. This happens because its tourism development still faces obstacles, namely the promotional strategy carried out is still traditional so that Bumiwangi village as a tourist village does not yet have an active promotion that shows the difference between Bumiwangi tourist village and other tourist villages. Even information about Bumiwangi village is still little found on digital platforms. In this study using qualitative research methods. The research approach taken is a qualitative approach with a descriptive type of research supported by observation and interviews with sources. This research aims to produce an in-depth understanding of the process of creating a website to promote and develop tourist villages. It is hoped that this research can provide important directions and insights for the development of Bumiwangi Tourism Village in terms of effective digital promotion and utilization of tourist interest information to improve the experience and attractiveness of tourist destinations.